WEBGIS EXTREME WEATHER AND HEALTH FACILITIES IN MAGELANG REGENCY - Mahasinul Akhlak, Muhammad Lutfi; Susilo, Gatot; Anggi Ariesta Kusuma, Ahmad Fauzi; Al Amin , Imam Husni (STMIK BINA PATRIA, 2026)
Magelang Regency, Indonesia, has a high potential for extreme weather disasters due to its unique geographical and hydrological characteristics. This study utilizes WebGIS technology to assess the readiness of healthcare facilities in areas prone to extreme weather events in Magelang Regency. The developed WebGIS platform displays: (1) administrative maps, (2) the spatial distribution of health facilities, (3) extreme weather risk, hazard, capacity, and vulnerability maps, and (4) an analytical identification of healthcare facility readiness. This website aims to provide accurate and informative spatial information to support decision-making in extreme weather disaster mitigation planning. User Acceptance Testing (UAT) involving 10 respondents yielded a score of 88.8% (out of 100%), indicating that users 'strongly agree' that the system meets user-friendly criteria